Nine new Zonopimpla Ashmead (Hymenoptera, Ichneumonidae, Pimplinae) and key to species from Venezuela - Valera, Neicy; Díaz, Francisco (Zootaxa, 2010)
Zonopimpla Ashmead is an exclusively Neotropical genus with the greatest number of species in Central America. In order to better understand the Zonopimpla species occurring in Venezuela, samplings using Malaise traps were conducted at six-months intervals in Aragua, Lara and Merida states in Venezuela from 2001–2003. Specimens from three major entomological museums were also examined. Nine new Zonopimpla species are described and illustrated: Z. diazi sp. nov., Z. moralesi sp. nov., Z. pereirai sp. nov., Z. pseudoatriceps sp. nov., Z. rodriguezi sp. nov., Z. sebastiani sp. nov., Z. torrellasi sp. nov., Z. vasquezi sp. nov., and Z. victoriae sp. nov. A taxonomic key for the Venezuelan species of Zonopimpla is provided, including also Z. atriceps (Cresson) and Z. fasciata Townes.